2015
DOI: 10.1016/j.jmir.2015.09.001
|View full text |Cite|
|
Sign up to set email alerts
|

Consistency of Organ Geometries during Prostate Radiotherapy with Two Different Bladder and Bowel Regimens

Abstract: Background: The majority of Ontario cancer centres incorporate bladder and bowel preparation protocols for the treatment of prostate cancer with radical radiotherapy. Differing methods are used to achieve a full bladder and empty rectum for planning and treatment. We compared the effects of two different bladder and bowel preparation regimens on bladder, rectum, and prostate þ/À seminal vesicle geometries through a course of radiotherapy. An optimal preparation would achieve reliable spatial arrangements and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 22 publications
(31 reference statements)
0
14
0
Order By: Relevance
“…Although previous studies seeking to find an optimal bladder and rectal state for prostate radiotherapy have not found significant differences in the intra‐fractional prostate displacement between plans that were designed for patients with full and empty bladders, they have not investigated displacement and change in the dose to the prostate between extreme bladder states. Our results showed that changes in the bladder volume can lead to large, systematic displacements in the prostate and SVs.…”
Section: Discussionmentioning
confidence: 99%
“…Although previous studies seeking to find an optimal bladder and rectal state for prostate radiotherapy have not found significant differences in the intra‐fractional prostate displacement between plans that were designed for patients with full and empty bladders, they have not investigated displacement and change in the dose to the prostate between extreme bladder states. Our results showed that changes in the bladder volume can lead to large, systematic displacements in the prostate and SVs.…”
Section: Discussionmentioning
confidence: 99%
“…Diet as a method of managing rectal variation has been investigated with mixed results. [26][27][28][29] Looking to influence the rectal volume and the presence of gas with dietary advice proved unfeasible in our local, small group study of patients receiving bladder radiotherapy. In total, 80% of patients self-identified comorbidity that required them to follow a specific diet.…”
Section: Study Rationalementioning
confidence: 97%
“…– 25 Micro-enemas have been used as standard practice within the author’s department for 15 years, and the assessment of patient suitability is made using Patient Group Directives. Diet as a method of managing rectal variation has been investigated with mixed results 26 29 Looking to influence the rectal volume and the presence of gas with dietary advice proved unfeasible in our local, small group study of patients receiving bladder radiotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…However, this protocol is not used in our department. Yaver et al indicated that bladder and rectum preparation can influence the geometries and volume of both organs and affect dose exposures and toxicities [17], and others indicated possible dosimetric variations affecting normal tissue complication probability [18,19,20]. The introduction of image guidance techniques using kilovoltage (kV/kV) and gold fiducial markers or kilovoltage conebeam computed tomography (kV-CBCT) imaging has brought about a reduction in toxicity [21] and help in finding out the daily variation in bladder and rectum volume due to variable filling during the course of treatment [22].…”
Section: Introductionmentioning
confidence: 99%